Subject in a Search of Event: Serguey Zhadan’s Poetry as an Expression of New Political Thought - Bylina, Evgeny (Przegląd Wschodnioeuropejski, 2018)
In our article we are analyzing the fact that literature is able to be a space of discovering collective subjectivity on the example of the poetry of Serguey Zhadan. The literary experience of Serguey Zhadan, one of the most well-known poets in modern Ukraine, emerges from the recent historical events – the war in the South-East of Ukraine, which started after the revolution – events, which emphasize the necessity to look at the crisis of post-Soviet identity in a new way. Adverting to the analysis of his poetry, we come to the following conclusion: the subject of his poetry takes his part in the nomadic movement between two poles attempting to overcome this crisis. On the one hand, due to appealing it appeals to the tradition and linguistic identity, and on the other hand – to the emancipatory left-wing politics. These poles mean the search of such an Event, which would allow saving unique national unity and the creation of the community, this would mean the true equality. At the end of the article, we conclude that poetic expression of Serguey Zhadan aims to represent the experience of private, unique life which is, at the same time, part of a collectivity and collective history.